Libet's experiment: A complex replication - Dominik, Tomáš; Dostál, Daniel; Zielina, Martin; Šmahaj, Jan; Sedláčková, Zuzana; Procházka, Roman (Consciousness and cognition, 2018)
Libet's experiment is an influential classical study, which does not stop provoking heated debates. However, a full-scale replication has not been carried out to this day. Libet-style studies have usually focused on isolated ideas and concepts and never on the whole experiment in all its complexity. This paper presents detailed methodological description and results of a complex replication study. The methodology follows Libet's directions closely in most cases; when it does not, the differences are described and elaborated. The results replicate Libet's key findings, but substantial differences were found in some of the results' categories, such as the introspective reports or the number of readiness-potentials found. The discussion also addresses some current problems pertaining the methodology of the Libet-style experiments and provides some recommendations based on a detailed process evaluation.
Keywords: dospělí; Contingent Negative Variation; Female; vědomí; hmatová percepce; kontingentní negativní variace; Psychomotor Performance; Adult; ženské pohlaví; mladý dospělý; Consciousness; pohybová aktivita; lidé; psychomotorický výkon; Self Report; Readiness-potential; vnímání času; uvědomování si; Subjective event timing; Touch Perception; Humans; Electromyography; Male; Young Adult; Time Perception; Motor Activity; Libet’s experiment; mužské pohlaví; zpráva o sobě; elektroencefalografie; Rotating-spot method; Replication; elektromyografie; Electroencephalography; Awareness